Portraits of Principal Practice: Time Allocation and School Principal Work. (February 2018) - Sebastian, James; Camburn, Eric M.; Spillane, James P.
Purpose: The purpose of this study was to examine how school principals in urban settings distributed their time working on critical school functions. We also examined who principals worked with and how their time allocation patterns varied by school contextual characteristics.Research Method/Approach: The study was conducted in an urban school district with approximately 50 school principals and utilized self-reported End of Day log data collected at multiple points in between 2005 and 2007. We utilized hierarchical linear models to analyze variation in principals' time allocation by time (hour, day, semester), school function (building operations, student affairs, district functions, etc.), and school personnel (self, teacher, student, etc.).Findings: Variation in principals' practice is domain dependent. Consistent with prior research, we find that a principal's workday is characterized by long hours and diverse tasks. We find little support for the notion that typical tasks are characterized by brevity. Principals also spend most of their time working with within-building colleagues rather than working alone. Of all predictors we examined in the study, only hour of the day predicts principals' time allocation on different functional domains.Conclusions: The portrait of principals' work described in this study expands and enriches the field's current understanding of how principals allocate their time across the multiple domains of responsibility that require their attention. We find that our data offer support for some of popular conceptions of principals' work described in the research literature while challenging other common conceptions.